2018
DOI: 10.1016/j.bbamem.2017.09.027
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of synergistic antibacterial activity of combined biosurfactants revealed by bacterial cell envelop damage

Abstract: Besides potential surface activity and some beneficial physical properties, biosurfactants express antibacterial activity. Bacterial cell membrane disrupting ability of rhamnolipid produced by Pseudomonas aeruginosa C2 and a lipopeptide type biosurfactant, BS15 produced by Bacillus stratosphericus A15 was examined against Staphylococcus aureus ATCC 25923 and Escherichia coli K8813. Broth dilution technique was followed to examine minimum inhibitory concentration (MIC) of both the biosurfactants. The combined e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(39 citation statements)
references
References 33 publications
2
36
0
1
Order By: Relevance
“…Sana et al . () showed that both E. coli and S. aureus were sensitive to rhamnolipid and that because of its’ hydrophilic and hydrophobic parts it interacts with the nonpolar part of the cell membrane. The membrane disintegrates leading to the penetration of the cell wall and plasma membrane by pore formation and subsequent leakage of inner cytoplasmic materials leading to cell death (Meincken et al .…”
Section: Antimicrobial and Antifungal Properties Of Biosurfactantsmentioning
confidence: 99%
See 3 more Smart Citations
“…Sana et al . () showed that both E. coli and S. aureus were sensitive to rhamnolipid and that because of its’ hydrophilic and hydrophobic parts it interacts with the nonpolar part of the cell membrane. The membrane disintegrates leading to the penetration of the cell wall and plasma membrane by pore formation and subsequent leakage of inner cytoplasmic materials leading to cell death (Meincken et al .…”
Section: Antimicrobial and Antifungal Properties Of Biosurfactantsmentioning
confidence: 99%
“…These mechanisms might help explain how the LP produced by B. stratosphericus (Sana et al . ) has an antibacterial effect against both S. aureus and E. coli .…”
Section: Antimicrobial and Antifungal Properties Of Biosurfactantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Instead, E. sakazakii cells were seen to have shrunk, producing a ruffled appearance to their membranes. The difference in these two results is likely attributable to the difference in cell membrane structure between the gram‐positive S. aureus and the gram‐negative E. sakazakii (Sana, Datta, Biswas, & Sengupta, ; Szabó et al, ).…”
Section: Resultsmentioning
confidence: 99%